FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY (Studi Empiris pada Perusahaan Sektor Jasa yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2011 dan 2012) - Suci Nasehati Sunaningsih; Abdul Rohman (Diponegoro Journal of Accounting, 2014)
Timeliness of financial reporting is one of important qualitative attributes that makes the information provided in financial statements useful to users. The reason that makes researcher interested in research in this field is that audit process can cause delay in reporting financial statements. The purpose of this research is to examine the impact of firm size, debt to asset ratio (DAR), earning per share (EPS), type of industry, auditor’s opinion, and reputation of public accountants toward audit delay.Data used is audited financial statements from Indonesian service companies (tertiary sector) that listed on Indonesia Stock Exchange in 2011 and 2012. Sampling method that used is purposive sampling. The samples consist of 157 financial statements from 101 service companies. Multiple linear regression is used to be an analysis technique.The results of this research indicate that earning per share (EPS) and auditor’s opinion have significantly negative influence to audit delay. However, other factors, such as firm size, debt to asset ratio (DAR), type of industry, and reputation of public accountants have no significant influence to audit delay.